MANAKIB, WALI DAN KERAMAT MENURUT ULAMA BANJAR - ., Rahmadi (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
1his writing attempts to expose the Banjarese ulema concept on manakib, the holi people, and the sacred in a descriptive way. From the study on the writings of Banjarese ulema about this topic, it is found that the tradition of manakib reading is sunnah hasanah ( a good tradition), has a lgligious bene6t, aad does not include an element that can ruin our faith. The holy person according to Banjarese ulema perspective is a person who knows Allah and has an extraordinary obedieoce and devotion, afraid of doing mistakes, has. karamah, and has hierarchy. The sacred according to the Banjarese ulema is an extraordinary event which is granted to the holy persoo by Allah. The highest sacred is istiqamah (maknawi sacred), while othet sacred can be in the form of al-khariq al-adah event Qrissi sacred) urhich has lower level.